2017
DOI: 10.1016/j.clon.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Mobilising Expertise and Resources to Close the Radiotherapy Gap in Cancer Care

Abstract: Closing the gap in cancer care within low-and middle-income countries and in indigenous and geographically isolated populations in high-income countries requires investment and innovation. This is particularly true for radiotherapy, for which the global disparity is one of the largest in healthcare today. New models and paradigms and non-traditional collaborations have been proposed to improve global equity in cancer control. We describe recent initiatives from within the radiation oncology community to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Tackling the radiotherapy burden in LMICs is a complex task that requires multidisciplinary collaboration [8], [9], [10]. An International Cancer Expert Corps sponsored workshop held on the CERN campus in 2016 invited experts from fields including oncology and accelerator physics to consider future options, including innovative technology, for tackling this global problem [11].…”
Section: Introductionmentioning
confidence: 99%
“…Tackling the radiotherapy burden in LMICs is a complex task that requires multidisciplinary collaboration [8], [9], [10]. An International Cancer Expert Corps sponsored workshop held on the CERN campus in 2016 invited experts from fields including oncology and accelerator physics to consider future options, including innovative technology, for tackling this global problem [11].…”
Section: Introductionmentioning
confidence: 99%
“…Reddy 11 reported that if capital costs and service were equal, then linear accelerator technology would be considered superior to cobalt technology for modern‐day curative radiotherapy. The working group also noted that, “… the cost of one military jet fighter represents the entire cost for establishing and maintaining a radiation therapy service for most countries.” We also need to look at cancer management from a global perspective 3,7,12 rather than a two‐ or three‐tier system for low‐income, middle‐income, and high‐income economies when addressing healthcare. We should focus on solutions driven by type and stage of cancer as well as the reasons for treatment.…”
Section: Against the Proposition: Godfrey Azangwe Phdmentioning
confidence: 99%
“… 6 Several international programmes have been launched over the last decade to address the need for additional RT machines in Africa, resulting in a steady increase in the number of megavoltage units being installed on the continent 7 and this in turn, has resulted in increased pressure to teach and train RT professionals to safely plan and operate the modern units and create safe clinical treatment plans. 8 …”
Section: Introductionmentioning
confidence: 99%